STUDI SEDIMENTASI DI MUARA SUNGAI ANGSANA KECAMATAN ANGSANA KABUPATEN TANAH BUMBU KALIMANTAN SELATAN - Rina Iskandar; Frans Tony (EnviroScienteae, 2013)
This research aims to study the sedimentation in the river estuary waters Angsana district. Angsana Tanah Bumbu regency. Influence the flow of the stream sediment is carried sediment toward the beach and left it on the beach to be affected by the waves.  Measurement results of the direction and speed of the flow field shows that the speed of the current (at the prodding shoreline position from west to east), showed that when the water towards the tide, the direction of the flow moving eastward with a maximum speed of 0.0595 m / s.  Whereas the at low tide current direction to move westward with a speed smaller 0.0108 m / s.  Shape, size and weight of the soil particles will determine the number and size of freight sedimen.  Angsana beach sediment grain dominant form of sand and gravel. The dominant type of sediment in the waters of Angsana sand (sand), with a percentage between 97.6% to 99.7%. Sediment transport volume is highest in the alongshore transport rate reached 1,455 cm3/jam with sediment heading East towards the sea.